Unburdening the (Dis)Connected Individual? A Digital Disconnection Policy Paradox in Flanders (Belgium) - Tom De Leyn; Alice Verlinden; Laura Lemahieu; Lore Geldof; Marthe Mennes; Arturo Cocchi; Marijn Martens; Mariek Vanden Abeele (Media and Communication)
The concept of digital disconnection, which refers to limiting digital media use for the sake of one’s well-being, has gained prominence in scholarly and public debates. Compared to a burgeoning digital disconnection industry that commodifies individuals’ struggles with constant connectivity, the development of evidence-based disconnection policies and regulations that support individuals to maintain digital well-being lags behind. The absence of digital disconnection policy may partly be due to a lack of studies investigating the contextual and institutional conditions in which policies and regulations are designed, implemented, and received. The few studies that do shed light on these conditions show that politicians’ and policymakers’ responses to digitalization involve discourses of individual responsibilization. Building on these insights, our study draws from in-depth interviews with 21 experts from organizations in Flanders (Belgium) who are responsible for digital well-being and digital disconnection across work, school, and family contexts. In particular, we have explored their perspectives on the challenges of constructing and implementing digital disconnection policies and regulations. Overall, the experts’ discourses reveal a conflict between striving for autonomy and the need for regulations concerning digital disconnection. This conflict leads to a digital disconnection policy paradox in which experts advocate for collective disconnection initiatives but ultimately resort to solutions on an individual level. We discuss the implications of our findings for the scholarly field of digital disconnection as well as for media policymakers.